Annealing Behavior of Vacancy‐Type Defects in Mg‐ and H‐Implanted GaN Studied Using Monoenergetic Positron Beams. Issue 10 (30th May 2019) - Uedono, Akira; Iguchi, Hiroko; Narita, Tetsuo; Kataoka, Keita; Egger, Werner; Koschine, Tönjes; Hugenschmidt, Christoph; Dickmann, Marcel; Shima, Kohei; Kojima, Kazunobu; Chichibu, Shigefusa F.; Ishibashi, Shoji
Abstract : Vacancy‐type defects in Mg‐implanted GaN with and without hydrogen (H) implantation are probed by using monoenergetic positron beams. Mg + and H + ions are implanted into GaN(000 1 ¯ ) to obtain 0.1 and 0.7‐µm‐deep box profiles with Mg and H concentrations of 1 × 10 19 and 2 × 10 20 cm −3, respectively. For the as‐implanted samples, the major defect species is determined to be Ga‐vacancy ( V Ga ) related defects such as V Ga, divacancy ( V Ga V N ), and their complexes with impurities. For Mg‐implanted samples, an agglomeration of vacancies starts at 800 °C annealing, leading to the formation of vacancy clusters such as ( V Ga V N )3 . For the samples annealed above 1000 °C, the trapping rate of positrons by vacancies is increased by illumination of a He–Cd laser. This is attributed to the capture of photon‐excited electrons by the defects and their charge transition. For Mg‐ and H‐implanted samples, the hydrogenation of vacancy‐type defects starts after 800 °C annealing. Comparing with the annealing behavior of defects for the samples without H‐implantation, the clustering of vacancy‐type defects is suppressed, which can be attributed to the interaction between Mg, H, and vacancies. Abstract : Vacancies in Mg‐ and H‐implanted GaN are probed by using monoenergetic positron beams. The hydrogenation of vacancy‐type defects starts after 800 °C annealing. Comparing with the annealing behavior of defects for the samples without H‐implantation, the clustering of vacancy‐type defects is suppressed, which can be attributed to the interaction between Mg, H, and vacancies.